EFFICIENCY OF USE OF ELECTRONIC TECHNOLOGIES IOT, AI, BLOCKCHAIN TECHNOLOGIES IN EXPORT DEVELOPMENT (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The efficiency of using electronic technologies such as IoT, AI, and blockchain in export development can have a significant impact on various aspects of the export process. The efficiency of using electronic technologies such as IoT (Internet of Things), AI (Artificial Intelligence), and blockchain technologies in export development can greatly enhance the overall process and outcomes.